Monitoraggio strutturale: Tecnologie laser per la Torre delle Milizie di Roma - Carlucci, Renzo; Bernardini, Fabrizio (GEOmedia, 2003)
Monitoraggio strutturale: Tecnologie laser per la Torre delle Milizie di Roma